Multi-Criteria Decision Making (MCDM) Approach for Selecting Solar Plants Site and Technology: A Review - Ghasempour, Roghayeh; Alhuyi Nazari, Mohammad; Ebrahimi, Morteza; Ahmadi, Mohammad Hossein; Hadiyanto, H. (Center of Biomass & Renewable Energy, Diponegoro University, 2019)
Renewable energies have many advantages and their importance is rising owing to gravely mounting concerns for environmental issues and lack of fossil fuels in the future. Solar energy, well acknowledged as an inexhaustible source of energy, is developing dramatically for different purposes such as desalination and electricity generation. Appropriate solar power plant is very important factor for power generation due to its cost and other constraints. The applied technology is as important as the solar power plants location.Â In this paper, a wide variety multi criteria decision making (MCDM) methods, investigated by various researchers, are presented to obtain effective criteria in selecting solar plants sites and solar plants technologies. There is not any comprehensive research providing all required criteria for decision making for site and technology selection. Based on the reviewed researches, weight of each criterion depends on many factors such as region, economy, accessibility, power network, maintenance costs, operating costs, etc. The important criteria for site selection are represented and investigated thoroughly in this review paper.Â© 2019. CBIORE-IJRED. All rights reservedArticle History: Received June 17th 2017; Received in revised form March 7th 2018; Accepted June 16th 2018; Available onlineHow to Cite This Article: Ghasempour, R., Nazari, M.A., Ebrahimi, M., Ahmadi, M.H. and Hadiyanto, H. (2019) Multi-Criteria Decision Making (MCDM ) Approach for Selecting Solar Plants Site and Technology: A Review. Int Journal of Renewable Energy Development, 8(1), 15-25.https://doi.org/10.14710/ijred.8.1.15-25